Corrective feedback: Pragmatic exposures in EFL classroom interactions - Darong, Hieronimus Canggung; Guna, Stanislaus (International Journal of Education and Learning, 2023)
The questioning act is considered to be one of the most common and prominent features of classroom interactions. This analysis was proposed to reveal teachers’ questioning acts serving as pragmatic exposures in their corrective feedback strategies as they interact with students in the classroom. Data were collected from two EFL teachers that conveniently observed so-called non-intrusive observation, taking notes, and audio-recording that was subsequently transcribed. Certain episodes obtained from transcription were chosen and scrutinized in light of how well they contributed to the aim of the study using Conversation Analysis (CA). As a result, this study has yielded important insights into what and how questions are. Through corrective feedback, teacher questions were not only regarded and associated with their pedagogical purposes but also with the pragmatic and social function depending on the context where and how they possibly appeared. Besides giving a contribution to the body of knowledge, the questioning act provides significance and brings solutions to problematic classroom interactions that most teachers might have in the class.